Sea Change at the FASB: From a Universal to a Stakeholder-Oriented Approach - Nathan S. Slavin; Jianing Fang (Journal of Accounting, Business and Management (JABM), 2022)
This paper studies the impact the Financial Accounting Standards Board’s (FASB) recent initiative to simplify accounting standards to reduce the cost of preparing financial reports by filers. Accounting standards have generally been uniform, particularly for profit-oriented companies and without consideration to the firm’s size. These standards applied equally to both private and public companies, primarily to enhance comparability in analyzing a firm’s performance. Various committees in the early part of the new millennium culminated in the establishment of the Private Company Council (PCC), an advisory unit to the FASB in supporting simplified accounting standards. The slogan of “one size fits all” has now shifted to “different strokes for different folks”. This study examines 179 accounting standards issued by the FASB from 2009-2019. The empirical results indicated that the FASB has promulgated many standards permitting simplified accounting procedures that have benefited both private and public companies since the establishment of the PCC. The last two years of our data demonstrates that the overwhelming number of accounting standards was focused on simplifying rules in an attempt to achieve cost savings for both private and publicly listed companies.